(untitled) (Polis (Santiago), 2018)
The present paper analyzes the subject–citizen representations articulated in Chilean expert discourse about citizenship. The methodological approach is a case study and a critical analysis of discourse, analyzing a sample of institutional documents of three influential Chilean Think Tanks: “Instituto Libertad y Desarrollo”, “Centro de Estudios Públicos” y “Fundación Chile 21”. The result identifies two subject-citizen positions: the “post-citizen subject” and the “neo-citizen subject”, concluding that both representations are articulated from a same political rationale